THE IMPACT OF DEFLATION ON FISCAL AGGREGATES - TRANDAFIR, Adina Violeta; NEGURIȚĂ, Octav; NEGURIȚĂ, Octav; GUNI, Claudia; GUNI, Claudia (Annals of Spiru Haret University. Economic Series, 2018)
This article addresses the phenomenon of deflation from a historical perspective, a phenomenon rarely encountered in our day. Deflation is generally defined as the fall in the aggregate level of the consumer price index, respectively, the reverse inflationary phenomenon. The article also presents, in addition to experiences in different countries in times when deflation has been more pronounced and longer, and the effects it may have on public finance aggregates. The paper analyses the literature of all time that deals with the subject, as well as a presentation of the empirical data recorded, and an econometric analysis wishing to highlight the impact that the aggregate index of prices may have on public debt, using data recorded in Romania during 2000-2017.